Pemanfaatan Augmented Reality (AR) Sebagai Media Pembelajaran Interaktif Pengenalan Huruf Hijaiyyah Berbasis Android - Nurkhalik Wahdanial Asbara (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2020)
The hijaiyyah letter is one of the lessons that must be learned for all Muslims. Through this augmented reality application for Hijaiyyah letter recognition, learning hijaiyyah letter recognition becomes more interesting and interactive so that users are more enthusiastic in recognizing and learning hijaiyyah letters. To improve the required data, the authors collect data through library research or literature study and field research or direct data collection on the object of research. After testing the augmented reality application system for Hijaiyyah letter recognition using the blackbox method, the application can display objects according to predetermined markers and can run well on mobile devices that have at least 2 GB of RAM. The recommended smartphone to use is a smartphone with a camera over 13 MP in order to be able to detect markers maximally and the time required to detect markers will be faster.